Homelessness among problem drug users: prevalence, risk factors and trigger events. - Kemp, P; Neale, J; Robertson, M (2006)
The present paper uses data from a prospective cohort study of 877 problem drug users entering treatment in Scotland to extend knowledge of homelessness and drug misuse in three important respects: First, the prevalence of homelessness among problem drug users is investigated; secondly, key risk factors for homelessness among problem drug users are identified; and thirdly, trigger events associated with movements into or out of homelessness by problem drug users over time are explored. Data were collected during two waves of interviewing which were conducted 8 months apart. Thirty-six per cent of problem drug users entering treatment were homeless at either or both interviews, a prevalence rate that is at least seven times greater than among the general population. Whilst many of the risk factors found to be associated with homelessness are common to homeless people in general, at least one homelessness risk factor - recent drug injection [OR = 1.40; 95% confidence interval (CI) = 1.01-1.96]- is clearly specific to those who take drugs. Movements into homelessness among problem drug users were associated with recently losing residency of children (OR = 2.28; 95% CI = 1.27-4.08), other recent family problems (OR = 1.88; 95% CI = 1.21-2.94) and worsening general health (OR = 2.17; 95% CI = 1.15-4.09). Movements out of homelessness were associated with not having recent family problems (OR = 0.43; 95% CI = 0.24-0.79). The findings provide empirical support for the good practice guidelines now being published by various UK Government departments, but also suggest that the relatives of problem drug users should be offered increased assistance to help them deal with the many stresses that having a drug-dependent family member can bring.